2016
DOI: 10.4045/tidsskr.14.1041
|View full text |Cite
|
Sign up to set email alerts
|

Polyheksanid – sikkerhet og effekt som antiseptikum

Abstract: BACKGROUND Polyhexamethylene biguanide hydrochloride/polyhexanide/polyaminopropyl biguanide (PHMB) is used as a disinfectant and antiseptic. This article discusses the use of the substance as an antiseptic. We summarise published data on its antimicrobial effect in vitro and its clinical effect and safety when used on skin, wounds and mucosa.MATERIAL AND METHOD A literature search was conducted in PubMed for articles published in the last five years. Articles available as of June 2014 were considered.RESULTS O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Unlike in prokaryotes, eukaryotic cells present greater compartmentalization and eject the biocide from the nucleus. Therefore, a greater Minimum Inhibitory Concentration (MIC) of PHMB is required for human eukaryotic cells than for the microorganisms’ prokaryotic cells; thus, human cells can withstand the concentrations of biocide required for decontamination [ 27 , 28 , 29 , 30 ].…”
Section: Biguanidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike in prokaryotes, eukaryotic cells present greater compartmentalization and eject the biocide from the nucleus. Therefore, a greater Minimum Inhibitory Concentration (MIC) of PHMB is required for human eukaryotic cells than for the microorganisms’ prokaryotic cells; thus, human cells can withstand the concentrations of biocide required for decontamination [ 27 , 28 , 29 , 30 ].…”
Section: Biguanidesmentioning
confidence: 99%
“…Machuca et al [ 27 ] demonstrated that PHMB-betaine solution was active against Gram-negative and Gram-positive bacteria, including biofilms of Klebsiella pneumoniae ST-716, Acinetobacter baumannii and S. aureus , all of which are of clinical concern due to rising antimicrobial resistance. This broad spectrum of activity both Gram-positive and Gram-negative bacteria has led to the use of PHMB against Mycobacterium species, including Mycobacterium smegmatis at an MIC of 5 mg/L for example [ 29 ]. Ongoing research aims to determine the suitability of PHMB as an antiseptic in wound dressings; Hübner et al [ 30 ] found that the presence of organic matter such as cartilage may affect the efficacy of PHMB against E. coli and S. aureus .…”
Section: Biguanidesmentioning
confidence: 99%
See 1 more Smart Citation
“…PHMB is a small molecule, with a characteristic carbon tail adjacent to a biguanide complex. PHMB's chemical structure closely resembles that of chlorhexidine, the most commonly used disinfectant and antiseptic of the skin prior to surgical operations [26]. At physiological pH, PHMB is polycationic due to the monoprotonation of each biguanide residue [27].…”
Section: Introductionmentioning
confidence: 98%
“…Polyhexamethylene biguanide (PHMB) is a polymer with the biocidal activity which is widely used as a preservative and as a broad-spectrum antiseptic. It is used as an antiseptic in the medical field in wound therapy [16], on skin and mucosa [17], and in eye disinfection [18][19][20][21][22][23]. In dentistry, PHMB is currently commercially available in mouthrinses and oral gels at various percentages up to 2% w/w [24].…”
Section: Introductionmentioning
confidence: 99%